2022
DOI: 10.1155/2022/7247549
|View full text |Cite|
|
Sign up to set email alerts
|

Application of Artificial Intelligence Nuclear Medicine Automated Images Based on Deep Learning in Tumor Diagnosis

Abstract: In order to correctly obtain normal tissues and organs and tumor lesions, the research on multimodal medical image segmentation based on deep learning fully automatic segmentation algorithm is more meaningful. This article aims to study the application of deep learning-based artificial intelligence nuclear medicine automated images in tumor diagnosis. This paper studies the methods to improve the accuracy of the segmentation algorithm from the perspective of boundary recognition and shape changeable adaptive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The knowledge gap addressed in this research is essential, as SCM studies and professionals have acknowledged the expanding application and influence of innovative tools to make business value and represent this value by obtaining a competitive advantage in the healthcare industry [ 41 ]. The importance of adopting these emerging technologies such as block chain [ 42 , 43 ], artificial intelligence [ 44 ], cloud computing [ 45 ], big data [ 46 ], and robotics [ 47 ], is emphasized in the SCM literature [ 40 ]. This research attempts to propose some resilience policies with novel technologies for SCM in healthcare by considering lessons learned from the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge gap addressed in this research is essential, as SCM studies and professionals have acknowledged the expanding application and influence of innovative tools to make business value and represent this value by obtaining a competitive advantage in the healthcare industry [ 41 ]. The importance of adopting these emerging technologies such as block chain [ 42 , 43 ], artificial intelligence [ 44 ], cloud computing [ 45 ], big data [ 46 ], and robotics [ 47 ], is emphasized in the SCM literature [ 40 ]. This research attempts to propose some resilience policies with novel technologies for SCM in healthcare by considering lessons learned from the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%